Less Welfare or Fewer Foreigners? Immigrant Inflows and Public Opinion towards Redistribution and Migration Policy - Elie Murard (Institute of Labor Economics (IZA), 2017)
I examine the effect of immigrant inflows in Europe on natives' individual attitudes towards redistribution and immigration policy over the last decade. Unlike previous studies, I analyze the evolution over time of these two types of attitudes in a joint empirical framework. Using migration data at the NUTS regional level from the European Labor Force Survey and individual attitudes data from the European Social Survey, I exploit variation over time and across regions in the size and composition of immigrant inflows. I address the endogeneity of immigrant inflows by using a shift share instrument and within-country specification. I find evidence coherent with a theoretical model in which individual attitudes depend essentially on how immigration is perceived to affect wages and net welfare benefits. Specifically, I find that, when immigrants tend to compete with natives for jobs (due to having similar skills or occupations), natives prefer policies that support welfare and put restrictions on migration. When migrants are mostly low-skilled (high-skilled), European citizens typically favor lower (higher) levels of redistribution.
Keywords: F22; F1; J61; 330; political economy; welfare state; immigration